Detecting resistance of trypanosomal infection to diminazene aceturate - a possible field test? - Rowlands, G.J. (European Union, 2000)
In this study, widespread resistance of T. congolense infections in East Highland Zebu cattle at Ghibe, southwest Ethiopia, to all available trypanocidal drugs has been demonstrated. Changes in incidence of T. congolense infections in cattle 36 months and more of age sampled between 1994 and 1997 at Ghibe when the number of negative samples is increased from 1 to 3 is presented in a table. A second table shows infection incidence and relapse rates in an average of 43 cows and 36 cows sampled monthly over 6 months at Ghibe.